МЕЂУНАРОДНИ ОБИЧАЈ У ЈУРИСПРУДЕНЦИЈИ СУДА ПРАВДЕ ЕУ - Đorđević Aleksovski, Sanja M. (Zbornik radova Pravnog fakulteta u Nišu, 2020)
By analysing the highly heterogeneous practice of the Court of Justice, one can identify four roles of international customary law within the EU legal order. Fistly, it has relatively frequently and easily been invoked for its demarcation role in order to differentiate the competences of EC/EU from its Member States'. It is notable that the Court of Justice did not refrain from this type of role of international customаry law. The interpretative role of international customary law is also not per se a contested one. However, it appears that the Court of Justice has only been keen to apply those customary provisions codified by the two Vienna conventions on the Law of Treaties, thus freeing itself from the burden of proving their existence or content. International customary law serves as a means of filling in legal gaps within EU law, thus having a praeter legem function. Јurisprudence has clarified that the invoking of international customary law in this function is only allowed when complementary to all other rules and principles of EU law. Finally, it has an important, yet not fully clarified derogatory role, when serving as a legal basis for challenging the validity of secondary legislation, which is in fact the most contested function. Throughout the years, by adding new requirements, the Court of Justice has defined a very high threshold. It is extremely cautious when granting the possibility of invoking international customary law in order to examine the validity of secondary legislation, thus (over)protecting the autonomy of EU law. Therefore, although the Court of Justice has repeatedly emphasized that international law is an integral part of the EU, there are different levels of invoking and applying international customary law in accordance with its different functions.